Inhaled corticosteroid use during pregnancy among women with asthma: A systematic review and meta‐analysis. Issue 11 (9th September 2019) - Robijn, Annelies L.; Jensen, Megan E.; McLaughlin, Karen; Gibson, Peter G.; Murphy, Vanessa E.
Abstract: Background: Studies demonstrate the prescription rate for inhaled corticosteroids (ICS) decreases in early pregnancy, possibly increasing exacerbation risk. This could be related to non‐adherence to prescribed asthma medication or medication cessation by the patient or doctor. ICS use during pregnancy has not previously been summarized in a systematic review. Objective: The aim of this systematic review and meta‐analysis was to evaluate the use of ICS during pregnancy among asthmatic women, specifically: (1) the prevalence of use, (2) changes of use during pregnancy compared with pre‐pregnancy and (3) medication adherence among ICS users. Methods: We systematically searched literature in Embase, MEDLINE, CINAL and Cochrane, using terms related to asthma, pregnancy and medication use. All English articles reporting ICS among pregnant women with asthma were included. Prevalence, changes in ICS use during pregnancy and ICS adherence were pooled using STATA (version 15.0, StataCorp USA). Results: A total of 4237 references were retrieved in the initial search. Screening and review led to the inclusion of 52 articles for one or more aims (Aim 1: N = 45; Aim 2, N = 13; and Aim 3, N = 5). The pooled prevalence of ICS use during pregnancy was 41% (95%CI 36%‐45%); 49% (95%CI 44%‐55%) in Europe, 39% (95%CI 32%‐47%) in Australia and 34% (95%CI 27%‐41%) in North America. In eight prescription databases, ICS prescription rates lowered in the first trimester of pregnancy, compared with pre‐pregnancy, increased in the second trimester and decreased in the third trimester. Five studies reported ICS adherence among pregnant women, using four measures of self‐reported non‐adherence. In two comparable studies, pooled ICS non‐adherence was 40% (95%CI 36%‐44%). Conclusions: The prevalence of ICS use among pregnant women with asthma is 41% and varies widely between countries and continents, and prescription rates for ICS change throughout pregnancy. More studies are needed to investigate ICS adherence during pregnancy in women with asthma.